Using the Pedicle Flap for Taking Pressure off the Pedicle in Distally Based Skin Flaps - Zhao, Jiaju; Wang, Peiji; Jiang, Bo (Journal of Reconstructive Microsurgery, 2013)
This report describes our experience using the pedicle flap for taking pressure off the pedicle in distally based skin flaps. Between July 2007 and March 2010, distally based skin flaps were used to treat 34 patients with soft tissue defects in the lower leg, ankle, and foot. A pedicle flap was used to take pressure off the pedicle in all of these flaps. There were 21 men and 13 women with a mean age at surgery of 47 years (range, 21 to 67 years). The sizes of the soft tissue defects varied from 5.0 cm × 2.0 cm to 17.0 cm × 10.0 cm. The pedicle flap sizes varied from 1.0 cm × 1.0 cm to 5.0 cm × 3.5 cm. All flaps survived completely except three, which suffered a marginal partial flap necrosis due to venous congestion. These flaps healed by secondary intention after changing the dressing. Using the pedicle flap takes pressure off the pedicle and facilitates primary closure after transposition of the distally based skin flaps, which is a simple and effective method to prevent complications of these flaps.
Keywords: distally based skin flaps; complications; lower extremity reconstruction